2015
DOI: 10.7287/peerj.preprints.1127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the attitudes of medical faculty members and students in Pakistan towards plagiarism: a cross sectional survey

Abstract: Objective:The objective of this survey was to explore the attitudes towards plagiarism of faculty members and medical students in Pakistan.Methods:The attitudes toward plagiarism questionnaire (ATPQ) was modified and distributed among 550 medical students and 130 faculty members in 7 medical colleges of Lahore and Rawalpindi. Data was entered in the SPSS v.20 and descriptive statistics were analyzed. The questionnaire was validated by principal axis factoring analysis.Results:Response rate was 93% and 73% resp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[11] Rathore et al have also reported that only one-quarter of students in the sample had formal training in medical writing and research ethics whereas most of the faculty members had received this training probably due to involvement in Continuing Medical Education (CME), self-directed learning and revision of faculty promotion rules. [17] Results of the current study have shown that 87.1% of the faculty members and 59.7% of senior residents were conducting research due to personal interest and this finding was found to have statistical significance for negative ATP.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…[11] Rathore et al have also reported that only one-quarter of students in the sample had formal training in medical writing and research ethics whereas most of the faculty members had received this training probably due to involvement in Continuing Medical Education (CME), self-directed learning and revision of faculty promotion rules. [17] Results of the current study have shown that 87.1% of the faculty members and 59.7% of senior residents were conducting research due to personal interest and this finding was found to have statistical significance for negative ATP.…”
Section: Discussionmentioning
confidence: 64%
“…These results are in consonance with those reported by Rathore et al from Pakistan. [17] Mean scores for positive domain, negative domain, and subjective norms of ATP scale were 30.54 ± 6.7, 24.34 ± 2.9, and 28.72 ± 6.6, respectively, in the current study. Pupovac et al also reported moderate positive attitude and subjective norms toward plagiarism with moderate to high negative attitude (36 ± 7, 26 ± 4, and 32 ± 6, respectively).…”
Section: Discussionmentioning
confidence: 85%